Patterns and Drivers of Phylogenetic Beta Diversity in the Forests and Savannas of Africa - Mathew Rees; Adeline Fayolle; John L. Godlee; Anais P. Gorel; David J. Harris; Kyle G. Dexter (Journal of Biogeography, 2025)
Aim Studying beta diversity, or the variation in species composition among communities, can give insights into plant community assembly over space and time. If different biomes show contrasting large‐scale beta‐diversity patterns, this can indicate divergent evolutionary histories or ecological processes that then drive species turnover among communities. Here, we examine phylogenetic beta‐diversity patterns across Africa in forest and savanna assemblages, the two most widespread tropical biomes on the continent. We hypothesise that savannas will show lower phylogenetic beta diversity due to their younger evolutionary history. Location Tropical Africa. Taxon Woody angiosperms. Methods We gathered 301,159 occurrences of woody angiosperms representing 1883 forest species and 1302 savanna species. We compared levels of phylogenetic beta diversity between forest and savanna assemblages, analysed spatial patterns of phylogenetic beta diversity using 1° grid cells and modelled their relationship with climate, disturbance and geographical distance. Results We found that savannas show greater relative regional phylogenetic beta diversity, whereas forest assemblages show greater relative local phylogenetic beta diversity. The spatial distribution of beta diversity showed strong East–West patterns for both forests and savannas, aligned with a major floristic discontinuity associated with the Albertine rift. Our results also highlighted West Africa as showing a high amount of compositional change for both biomes, arranged along an aridity gradient. Variance partitioning showed that predictors linked to precipitation were the main drivers of compositional change for both forests and savannas, but the importance of individual predictors was different in each biome. Main Conclusions Contrary to our expectations, our results indicate that savannas may have a deeper and richer evolutionary history than suggested by previous studies and that individual regions of both forest and savanna have high conservation value. Finally, our results demonstrate that environmental filtering is the dominant force influencing the assembly of these two important biomes at a continental spatial scale.

Characterising the biophysical, economic and social impacts of soil carbon sequestration as a greenhouse gas removal technology - Alasdair J. Sykes; Michael Macleod; Vera Eory; Robert M. Rees; Florian Payen; Vasilis Myrgiotis; Mathew Williams; Saran Sohi; Jon Hillier; Dominic Moran; David A. C. Manning; Pietro Goglio; et al. (Global Change Biology, 2020)
To limit warming to well below 2°C, most scenario projections rely on greenhouse gas removal technologies (GGRTs); one such GGRT uses soil carbon sequestration (SCS) in agricultural land. In addition to their role in mitigating climate change, SCS practices play a role in delivering agroecosystem resilience, climate change adaptability and food security. Environmental heterogeneity and differences in agricultural practices challenge the practical implementation of SCS, and our analysis addresses the associated knowledge gap. Previous assessments have focused on global potentials, but there is a need among policymakers to operationalise SCS. Here, we assess a range of practices already proposed to deliver SCS, and distil these into a subset of specific measures. We provide a multidisciplinary summary of the barriers and potential incentives towards practical implementation of these measures. First, we identify specific practices with potential for both a positive impact on SCS at farm level and an uptake rate compatible with global impact. These focus on: (a) optimising crop primary productivity (e.g. nutrient optimisation, pH management, irrigation); (b) reducing soil disturbance and managing soil physical properties (e.g. improved rotations, minimum till); (c) minimising deliberate removal of C or lateral transport via erosion processes (e.g. support measures, bare fallow reduction); (d) addition of C produced outside the system (e.g. organic manure amendments, biochar addition); (e) provision of additional C inputs within the cropping system (e.g. agroforestry, cover cropping). We then consider economic and non‐cost barriers and incentives for land managers implementing these measures, along with the potential externalised impacts of implementation. This offers a framework and reference point for holistic assessment of the impacts of SCS. Finally, we summarise and discuss the ability of extant scientific approaches to quantify the technical potential and externalities of SCS measures, and the barriers and incentives to their implementation in global agricultural systems.